The influence of parental career interests on adolescents' career choices - Sher, Dalene Philippa (My University, 2014)
The impact of parental interests on their children is a very important aspect of the career decision-making process of adolescents. The aim of this study was to find further support for this claim on knowledge, exploring the influence of both the mother and the father, If parents have any influence over their children’s career choices, one expects a high congruence between their interests. To investigate whether parents impact on career choices of their children congruencies in interest based on Holland’s (1985) model were analysed. According to Holland, an individual’s occupational interests are classified by means of a three-letter code, with each letter representing one of six personality types - Realistic, Investigative, Artistic, Social, - ^ Enterprising, Conventional. Therefore, three-letter codes obtained from the results of girls’ and their parents’, and boys’ and their parents’ completed Self-Directed Search Questionaries, formed the basis for investigating congruencies. The lachan Index (1984) was used to interpret raw data - a precise technique for the assessment of the degree of agreement between any two three-leltcrcodep. The mefAk v :^eement scores for the mother-daughter, mother-son, father-son, and father-daughter g ro u p ^ d n d t point to a close match between pairs of three-letter Holland codes, regardless of single sex or;%-educational schooling. The only significant difference in mean, agreement scores between these groups was between the father-son and father-daughter groups - fathers are more congruent to sons that&|a%#§rs in their interests. Resultant mean agreement scores between three-letter codes and occupations qf mothers and fathers did not point to a close tiiatch. This superficially does ntitsupport Holland’s (1985) theory of vocational choice that one’s occupation must fit one’s interests. There was also no significant difference between mean agreement scores0 ^m others and fatheps in this regard, supporting research that Holland’s (1985) theory is relevant to the female population. Cross-tabulations revealed that females aligned themselves most frequently with the Social Type, and males most frequently chose the Enterprising Type. This result was in accordance with previous studies and popular theory on sex stereotypes. The conclusion was drawn that no generalisation can be made about whether parents do or do not have an influence on their children’s occupational interests and subsequent career choices.